Characteristics of children with secondhand smoking - Septian Emma Dwi Jatmika; Muchsin Maulana (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2017)
Background: Passive smoking has been known to be associated with the risks of several diseases. Children are a group vulnerable to becoming passive smokers through adjacent adult smokers. Objective: To describe the characteristics of children with secondhand smoking. Methods: This research is a descriptive study involving 39 subjects of grade 4, 5, and 6 elementary school students. Inclusion criteria are having no subjective complaints of respiratory disturbances in the last 1 month, not smoking, living with parents/guardians/other family members that smoke inside the house, and willing to become respondents. Meanwhile, exclusion criterion was not returning the questionnaire. Samples were collected using purposive sampling technique. This study was conducted at Banguntapan Public Elementary School, Bantul in Agustus-September 2015. Instruments used in this study included questionnaires and spirometer. Data were analyzed univariately using frequency distribution. Results: More than half of the respondents were ≥ 11 years of age, female in gender, had parents that were ≥ 40 years of age, had parents that worked as labors, lived with one smoking family member, had parents that had started smoking at the age of < 24 years old, had parents that smoked ≥ 9 cigarettes per day, had parents that smoke outside the house, had parents that are mild smokers, and were not exposed to cigarette smoke. The highest level of education of the respondents’ parents was mostly (43.6%) senior high school. Subjective complaints of respiratory disturbances were reported by 74.4% of the respondents. Conclusion: Although no significant signs and symptoms of secondhand smoking were found, children that lived with smoking family members still need to be kept on watch. This is because more than half of the respondents of this study were reporting complaints of respiratory disturbances. Therefore, it is necessary to control the cigarette consumption of parents/ guardians, especially of those who still smoke inside the house.